Genome-Wide Analysis of AP2/ERF Superfamily Genes in Contrasting Wheat Genotypes Reveals Heat Stress-Related Candidate Genes - Magar, Manu Maya; Liu, Hui; Yan, Guijun (Frontiers in Plant Science, 2022)
The AP2/ERF superfamily is one of the largest groups of transcription factors (TFs) in plants which plays important roles in regulating plant growth and development under heat stress. A complete genome-wide identification, characterization, and expression analysis of AP2/ERF superfamily genes focusing on heat stress response was conducted in bread wheat. This study identified 630 putative AP2/ERF superfamily TF genes in wheat, with 517 genes containing well-defined AP2-protein domains. They were classified into five sub-families, according to domain content, conserved motif, and gene structure. The unique genes identified in this study were 112 TaERF genes, 77 TaDREB genes, four TaAP2 genes, and one TaRAV gene. The chromosomal distribution analysis showed the unequal distribution of TaAP2/ERF genes in 21 wheat chromosomes, with 127 pairs of segmental duplications and one pair of tandem duplication, highly concentrated in TaERF and TaDREB sub-families. The qRT-PCR validation of differentially expressed genes (DEGs) in contrasting wheat genotypes under heat stress conditions revealed that significant DEGs in tolerant and susceptible genotypes could unequivocally differentiate tolerant and susceptible wheat genotypes. This study provides useful information on TaAP2/ERF superfamily genes, and reveals candidate genes in response to heat stress, which forms a foundation for heat tolerance breeding in wheat.